Perbedaan Kekuatan Tarik Bahan Adhesif Total-Etchdengan Bahan Adhesif Self-Etchpada BondingBraket Ortodonsi (The Difference of Tensile Strength Between Total-Etch Adhesive Material and Self-Etch Adhesive Material for Orthodontic Bracket Bonding) - Dita Nur Ekasari; Herniyati .; Dwi Prijatmoko (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Background.Orthodontic treatment using a bracket attached to the teeth dentofasial aiming to get a good look aesthetically. At the beginning of orthodontic bracket bonding systems to enamel surface through several stages of work so that they can spend time, includes teeth cleaning, basting phosphoric acid etching, washing with water, drying, basting material bonding / primer, and application of composite resin as a bracket adhesive material called total-etch technique. But as the times have found self-etch adhesive that further simplify the time and phases of work, the incorporation of phosphoric acid etching and bonding materials / primer in one package. Tensile strength is the strong adhesive tensile or the ability of an object to hold while receiving an attractive force and the force coming from the direction perpendicular to the surface of the object, for example when there is an attractive force toward the labial or buccal tooth driven. Purpose. This study aimed to determine differences in tensile strength and know the best adhesive that can be used between total-etch adhesive with a self-etch adhesive on orthodontic bracket bonding. Methods.This study used 16 pieces mandibular firstpremolars were divided into two groups, each consisting of eight teeth. The first group used a total-etch adhesive, while the latter uses self-etch adhesive. Bracket adhesive tensile strength was measured using Torsee's Digital System Universal Testing Machine. Results.Independent t-test showed a significant difference between groups in total-etch adhesive with a self-etch adhesive (p <0.05). Conclusions and suggestions.There is a significant difference in tensile strength measurements of total-etch adhesive with adhesive and self-etch adhesive total-etch proved better than a self-etch adhesive on orthodontic bracket bonding. Further research needs to be done with respect to the composite resin material used, the stages of research, and tools used tensiletest. Keywords:bonding, self-etch adhesive, tensile strength, total-etch adhesive